Corticomotor excitability after two different repetitive transcranial magnetic stimulation protocols in haemorrhagic stroke patients - Asrarul Fikri Hassan; Muhammad Hafiz Hanafi; Zamzuri Idris; Jafri Malin Abdullah; Saiful Azli Nayan; Norhidayah Abd Aziz (Interdisciplinary Neurosurgery, 2020)
Intracerebral haemorrhage (ICH) or haemorrhagic stroke can be managed medically or by surgical evacuation of the hematoma. However, several authors have reported no significant difference when compared between both interventions in haemorrhagic stroke patients. We aimed to assess the use of Transcranial Magnetic Simulation (TMS) as supportive of medical and surgical interventions to assist the rehabilitation process in haemorrhagic stroke patient. A randomized control trial was performed on twenty nine patients and randomized into three groups; (1)Facilitatory, (2)Inhibitory and (3)Sham group. Patient underwent two weeks of TMS Stimulation protocol for total of 10 sessions. The pre and post Motor Evoked Potential (MEP) reading between groups were compared and analyzed. Our result indicated that regardless of patient’s age and ICH clot size, the improvement in MEP score after TMS facilitatory protocol was significantly higher compared to the Sham protocol group (p = 0.02). Such correlation however, was not observed in the inhibitory protocol group (p = 0.175). Collectively, our finding had demonstrates TMS potential as a safe and non-invasive tool for supportive management of ICH stroke as patients and that patient with stable ICH will have better motor function recovery post rTMS facilitatory protocol regardless of their age and clot size. Keywords: Transcranial magnetic stimulation, Motor evoked potential, Intracranial haemorrhage, Stroke rehabilitation, Facilitatory, Inhibitory